Pre- and postsynaptic serotonergic differences in males with extreme levels of impulsive aggression without callous unemotional traits: a positron emission tomography study using (11)C-DASB and (11)C-MDL100907. - Rylands, A; Hinz, R; Jones, M; Holmes, SE; Feldmann, M; Brown, G; McMahon, A; Talbot, P (2012)
BACKGROUND: Impulsive aggression (IA) in adults is associated with brain serotonin (5-HT) system abnormalities and is more common following childhood adversity. Within aggressive behavior, IA and callous unemotional (CU) traits are core components of differentiable factors with opposing 5-HT abnormalities. We aimed to investigate 5-HT abnormalities in IA and potential correlations with severity of childhood adversity while controlling for confounding 5-HT effects of high CU traits and mental disorders. METHODS: Healthy male subjects (mean age 34 ± 9 years) without high CU traits were recruited with IA ratings in the high (n = 14) and low (n = 13) population extremes. Serotonin transporter (SERT) and 5-HT(2A) receptor availability was measured in multiple brain regions using positron emission tomography with (11)C-DASB and (11)C-MDL100907, respectively, and compared between high-IA and low-IA groups. Correlations were measured between SERT and 5-HT(2A) receptor availability, impulsivity and aggression, and childhood adversity. RESULTS: Compared with the low-IA group, SERT were significantly higher in brainstem regions in the high-IA group (by 29.0% ± 11.4%) and modestly lower across cortical regions (by 11.1% ± 6.0%), whereas 5-HT(2A) receptors were also modestly lower (by 8.6% ± 4.0%). Across all subjects, brainstem SERT were significantly positively correlated with impulsivity, aggression, and childhood trauma ratings. Within the high-IA group, higher brainstem SERT was most strongly predicted by severity of childhood trauma (r = .76 in midbrain). CONCLUSIONS: Pre-and postsynaptic 5-HT differences are present in men with high levels of IA and are strongly suggestive of a persisting effect of childhood adversity on serotonergic neurodevelopment and emotional-behavioral control.